An Experience-Sampling Study on Academic Stressors and Cyberloafing in College Students: The Moderating Role of Trait Self-Control - Zhou, Bingping; Li, Ye; Tang, Yun; Cao, Wentao (Frontiers in Psychology, 2021)
Student cyberloafing is a relatively new educational phenomenon and is getting to be an outstanding issue that educators have to face. It is necessary to find out important factors that aggravate cyberloafing. Using an experience sampling method, this study examined the relationship between academic stressors and cyberloafing. Once a week for five consecutive weeks (T1–T5), 134 undergraduate students assessed the extent of academic stressors and cyberloafing of that week through an electronic questionnaire. Additionally, participants completed a trait self-control scale at Time 2. Results of two-level regression analysis showed that academic stressors were negatively associated with cyberloafing at the within-person level (i.e., week-to-week changes), but not at the between-person level. Furthermore, this relationship pattern was only observed in students with low trait self-control, while those with high trait self-control were less likely to cyberloaf regardless of academic stressors. These findings suggest that cyberloafing can fluctuate over periods, especially for individuals who lack self-control. Future research should consider cyberloafing from a dynamic perspective of individual-context interaction. Several practical implications are also discussed.